Prevalence of ixodid ticks and trypanosomosis in camels in southern rangelands of Ethiopia - Gebre, S.; Mekonnen, S.; Kaaya, G.P.; Tekle, T.; Jobre, Y. (2004)
The prevalence of ixodid ticks and trypanosomosis of camels was studied in the semi-arid rangelands of southern Ethiopia between 1995 and 1996. A total of 24077 ticks were collected from 510 camels aged between 6 months and 15 years. Eleven species of ticks were identified. Rhipicephalus pulchellus (59.1 %) was the most abundant tick followed by Hyalomma dromedarii (21.2%), Amblyomma gemma (12.5%), Hyalomma marginaturn rufipes (3.5%) and Hyalomma truncatum (2.8%). The highest numbers of ticks on camels occurred during the months from February to May with a peak during April. The other identified tick species were in very small numbers. Blood smears from 320 clinically sick camels were examined for haemoparasites out of which 142 (44.4%) were infected with Trypanosoma evansi, 3 (0.93%) with T. congolense and 2 (0.63%) with T. brucei. No tick-borne haemoparasites were detected. The possible ways of controlling ticks and trypanosomosis (T. evansi) in camel population are discussed in line with the livestock production system and climatic condition of the study area.